Medicinal Plants and their Uses Against Gastrointestinal Disorders in Pokhara - Dwa, Om Prasad (Kalika Journal of Multidisciplinary Studies, 2022)
The paper describes the uses of local plants against GI problems in Pokhara Valley. The findings of the study are based on the experience and indigenous knowledge of people rather than clinical or scientific evaluation. This execution tries to highlight the significance of traditional medicinal plants for the treatment of major health issues i.e. GI problems in Pokhara valley of Nepal. Many studies on the medicinal uses of plants show that traditional medicine is an integral part of rural Nepal. According to the result, rural people of Pokhara valley use 101 plants belonging to 61 families. Listed families are Acanthaceae, Amaranthaceae, Anacardiaceae, Apocynaceae, Araceae, Aclepidaceae, Aspidaceae, Asteraceae, Berberidaceae, Bignoniaceae, Bombacaceae, Cannabinaceae, Cappridaceae, Caricaceae, Caryophyllaceae, Chenopodiaceae, Combretaceae, Commelinaceae, Crassulaceae, Cuscutaceae, Cyperaceae, Dioscoreaceae, Dipterocarpaceae, Elaeagnaceae, Euphorbiaceae, Fabaceae, Gentianaceae, Lamiaceae, Lauraceae, Liliaceae, Linaceae, Lythraceae, Magnoliaceae, Malvaceae, Meliaceae, Menispermaceae, Musaceae, Moraceae, Myricaceae, Myrtaceae, Nephrolepidaceae, Nyctaginaceae, Nymphaeaceae, Oxalidaceae, Pinaceae, Piperaceae, Poaceae, Polygonaceae, Punicaceae, Rhamnaceae, Rosaceae, Rutaceae, Sapindaceae, Solanaceae, Theaceae, Trapaceae, Ulmaceae, Umbelliferae, Urticaceae, Vitaceae, Zingiberaceae.